Tuberculous lymphadenitis in HIV infection. Histological findings - Arévalo, Fernando (2006)
Introduction: Coinfection of human virus immunodeficiency (VIH) and tuberculosis changes the histological features of tuberculosis; this is particularly frequent in tuberculous lymphadenitis. Objective: To identify main histological diferences between tuberculous lymphadenitis associated to VIH and not associated to VIH. Design: Descriptive, transversal, comparative stufy. Setting: Pathological Anatomy Service, Dos de Mayo Hospital. Participants: Patients with tuberculous lymphadenitis associated or not to VIH. Interventions: Study of histological differences between lymphadenitis tuberculosis associated with HIV and non associated with HIV, during 2005 and first half of 2006. Main outcome measures: Histological presentation of tuberculosis. Results: Twenty-two cases of tuberculous lymphadenitis were identified, 27,3% showed VIH coinfection; caseum necrosis was identified in 83,3% of cases HIV-associated and in 100% of nonHIV associated cases (p=0,00). Koch bacillus was identified in 50% of associated HIV cases and it was not identified in any non related HIV case (p=0,01). We also found an attributable risk of 52,3% for the development of caseum necrosis and presence of Langhans cells. Conclusions: We found higher presence of mycobacterium in HIV positive patients and higher presence of caseum necrosis in HIV negative patients.